Gambaran Perilaku Masyarakat dalam Upaya Pencegahan Demam Berdarah Dengue di Wilayah Kelurahan Sidomulyo Timur Marpoyan Damai - Fitria Mardhotilah; Arneliwati Arneliwati; Febriana Sabrian (Pusat riset dan Inovasi Nasional, 2026)
Introduction: Dengue Hemorrhagic Fever (DHF) is a serious disease transmitted by the aedes aegypti mosquito. Dengue Hemorrhagic Fever (DHF) is an infectious disease transmitted through the bite of the Aedes aegypti mosquito and is still a public health problem. The high incidence of dengue fever is often caused by a lack of knowledge, attitudes, and actions of the community in carrying out appropriate prevention efforts. The goal is to identify the picture of community behavior in dengue prevention, including aspects of knowledge, attitudes, and actions. Method: was a quantitative descriptive with 100 respondents selected by random sampling in East Sidomulyo Village, Marpoyan Damai. Data were collected through questionnaires and analyzed univariately. Results: The variables of community behavior were obtained in the knowledge of most of the people who were low as many as 52 respondents (52%), most of the people's attitudes were obtained negative attitudes as many as 77 respondents (77%), the actions of the community mostly had less actions with the number of 59 respondents (59%), and the behavior of the community was relatively low. Conclusions and Suggestions: This study shows that the majority of the people of East Sidomulyo Village have lacking knowledge, attitudes, and actions in the prevention of dengue. Low preventive behavior is caused by a lack of knowledge and concern. Intensive, community based education is needed to raise awareness and preventive measures in an ongoing manner.